Does attribute amnesia occur with the presentation of complex, meaningful stimuli? The answer is, "it depends". - Chen, Hui; Yu, Jiahan; Fu, Yingtao; Zhu, Ping; Li, Wei; Zhou, Jifan; Shen, Mowei (Memory & Cognition, 2019)
Attribute amnesia (AA) is a recently reported phenomenon whereby participants are unable to report a salient attribute of a stimulus (e.g., the color or identity of a target letter) on which their attention has just been focused during a prior task. This counterintuitive effect has been repeatedly replicated with various simple stimuli such as digits and letters. The current study sought to explore boundaries of AA by investigating whether the phenomenon persists when participants encounter complex, meaningful stimuli (e.g., pictures) that have been shown to hold an advantage in cognitive processing and memory. In Experiments 1a–d, we examined whether AA was observed with different types of complex stimuli. In Experiments 2a–b and 3a–b, we linked the type of stimuli (simple vs. complex and meaningful stimuli) to the other two potential boundary factors of AA (i.e., repetitiveness of target stimulus and set effects of Einstellung) to see whether there were interactions between stimuli type and these two boundary factors. The results demonstrated that the AA effect was still consistently observed for complex stimuli in a typical AA paradigm wherein participants encountered many trials and the targets were repeated across trials. However, this effect only appeared for simple stimuli, but not for complex stimuli in two special cases: when target stimuli were never repeated through the experiment, or when the surprise test was placed on the first trial of the experiment. These findings have crucial implications in understanding the boundaries of the AA phenomenon.